The Urgency of Institutional Development of Cassava Industry in Daerah Istimewa Yogyakarta and Jawa Tengah - Maulida, Yuhan Farah; Subejo; Hardyastuti, Suhatmini (Sodality: Jurnal Sosiologi Pedesaan, 2021)
The study shows that there was variation in the process of cassava-based food production. In Daerah Istimewa Yogyakarta (DIY) and Central Java, the farming systems were still subsistence oriented as the members still carried out traditional farming and worked without practicing intensive farming. However, the cassava-based food processing had already been commercially oriented. Some farmers have successfully collaborated with the larger cassava industry who were profit and commercially oriented. Some agribusiness units required specific varieties, but others opened to any varieties of cassava. The various arrangements have created different patterns of partnership. There were three types of business partnerships namely (1) growers and small-scale manufacturers; (2) partnership among growers, raw material processors, food manufacturers, and distributors or sellers; and (3) partnership among growers, small or large manufacturers and distributors or sellers. Among those three patterns, some enterprises had already performed a business-oriented processing method and quality assurance which requires best quality of raw cassava. This is resulted in a better selling price. Business partnerships can guarantee the sustainability of business relationships among business units. A better upstream-downstream relation needs to be developed to prevent the risks of raw materials supply.